Synthesis and hydrogenation of polycyclic aromatic hydrocarbon-substituted diborenes via uncatalysed hydrogenative B–C bond cleavage. Issue 25 (14th June 2022) - Okorn, Alexander; Jayaraman, Arumugam; Englert, Lukas; Arrowsmith, Merle; Swoboda, Theresa; Weigelt, Jeanette; Brunecker, Carina; Hess, Merlin; Lamprecht, Anna; Lenczyk, Carsten; Rang, Maximilian; Braunschweig, Holger
Abstract : In contrast to classical B–B bond-centred diborene hydrogenation, polycyclic aromatic hydrocarbon-substituted diborenes first undergo thermal intramolecular hydroarylation, followed by hydrogenation of the remaining B–B and endocyclic B–C bonds. Abstract : The classical route to the PMe3 -stabilised polycyclic aromatic hydrocarbon (PAH)-substituted diborenes B2 Ar2 (PMe3 )2 (Ar = 9-phenanthryl 7-Phen ; Ar = 1-pyrenyl 7-Pyr ) via the corresponding 1, 2-diaryl-1, 2-dimethoxydiborane(4) precursors, B2 Ar2 (OMe)2, is marred by the systematic decomposition of the latter to BAr(OMe)2 during reaction workup. Calculations suggest this results from the absence of a second ortho -substituent on the boron-bound aryl rings, which enables their free rotation and exposes the B–B bond to nucleophilic attack. 7-Phen and 7-Pyr are obtained by the reduction of the corresponding 1, 2-diaryl-1, 2-dichlorodiborane precursors, B2 Ar2 Cl2 (PMe3 )2, obtained from the SMe2 adducts, which are synthesised by direct NMe2 –Cl exchange at B2 Ar2 (NMe2 )2 with (Me2 S)BCl3 . The low-lying π* molecular orbitals (MOs) located on the PAH substituents of 7-Phen and 7-Pyr intercalate between the B–B-based π and π* MOs, leading to a relatively small HOMO–LUMO gap of 3.20 and 2.72 eV, respectively. Under vacuum or at high temperature 7-Phen and 7-Pyr undergo intramolecular hydroarylation of the BB bond to yield 1, 2-dihydronaphtho[1, 8- cd ][1, 2]diborole derivatives. Hydrogenation of 7-Phen, 7-Pyr and their 9-anthryl and mesityl analogues III and II, respectively, results in all cases in splitting of the B–B bond and isolation of the monoboranes (Me3 P)BArH2 . NMR-spectroscopic monitoring of the reactions, solid-state structures of isolated reaction intermediates and computational mechanistic analyses show that the hydrogenation of the three PAH-substituted diborenes proceeds via a different pathway to that of the dimesityldiborene. Rather than occurring exclusively at the B–B bond, hydrogenation of 7-Ar and III proceeds via a hydroarylated intermediate, which undergoes one B–B bond-centered H2 addition, followed by hydrogenation of the endocyclic B–C bond resulting from hydroarylation, making the latter effectively reversible.